2020
DOI: 10.21203/rs.3.rs-23751/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between psoriasis and migraine: what should we expect from a meta-analysis?

Abstract: Background Although many studies have demonstrated the commodity of psoriasis with migraine and indicated that they may have similar susceptibility genes and pathophysiologic mechanism, the clinic association between the migraine and psoriasis remains unclear. Methods We have already searched Pubmed, Embase, and Web of Science for case–control, cross-sectional, or cohort studies, and extract rate, odds or risk of migraine in subjects with psoriasis or without psoriasis. Using defined inclusion and exclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This study indicated a significant association between migraine and psoriasis OR 1.64 (95% CI 1.28; 2.11). Although the underlying causes for this association have not been observed, pathophysiological, molecular, and therapeutic aspects should be considered explanatory factors ( 306 ). Migraine with aura (MA) is an independent risk factor for the cardiovascular system (CV) in people under 45 years of age ( 307 , 308 ), and the number of MA crises is a sign of the severity of CV ( 309 , 310 ).…”
Section: Methodsmentioning
confidence: 99%
“…This study indicated a significant association between migraine and psoriasis OR 1.64 (95% CI 1.28; 2.11). Although the underlying causes for this association have not been observed, pathophysiological, molecular, and therapeutic aspects should be considered explanatory factors ( 306 ). Migraine with aura (MA) is an independent risk factor for the cardiovascular system (CV) in people under 45 years of age ( 307 , 308 ), and the number of MA crises is a sign of the severity of CV ( 309 , 310 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the results of a recent meta-analysis also indicated the increased risk of migraine in psoriatic patients compared to the non-psoriatic control group (OR = 1.64, 95% CI 1.28‒2.11). 31 …”
Section: Discussionmentioning
confidence: 99%